Origins of the Earth, Moon, and life an interdisciplinary approach - Makishima, Akio (Elsevier, 2017)
Origins of the Earth, Moon, and Life: An Interdisciplinary Approach presents state-of-the-art knowledge that is based on theories, experiments, observations, calculations, and analytical data from five astro-sciences, astronomy, astrobiology, astrogeology, astrophysics, and cosmochemistry. Beginning with the origin of elements, and moving on to cover the formation of the early Solar System, the giant impact model of the Earth and Moon, the oldest records of life, and the possibility of life on other planets in the Solar System, this interdisciplinary reference provides a complex understanding of the planets and the formation of life. Synthesizing concepts from all branches of astro-sciences into one, the book is a valuable reference for researchers in astrogeology, astrophysics, cosmochemistry, astrobiology, astronomy, and other space science fields, helping users better understand the intersection of these sciences.--Provided by publisher.